Political Corruption as a Systemic Issue: Its Impact on Poverty, Inequality, and Development in Nepal - Thapa, Santa Bahadur (Prajnik Bimarsha प्राज्ञिक विमर्श, 2025)
This paper examines the profound impact of political corruption on Nepal’s socioeconomic development, a landlocked country struggling with pervasive corruption. The significance of this study lies in its comprehensive, evidence-based discussion, highlighting how corruption undermines development indicators, social metrics, and erodes public trust. The methodology employs a mixed-methods approach, combining a qualitative analysis of prominent corruption scandals with a quantitative analysis of socioeconomic indicators and public expenditure data to establish a correlation between corruption and development outcomes. Significant findings reveal that corruption is a systemic issue, not merely a symptom, that exacerbates poverty and inequality by diverting resources from the populace. While governmental and non-governmental anti-corruption initiatives exist, their effectiveness is limited by a lack of political will and deeply ingrained patronage networks. The paper concludes that tackling corruption is a fundamental prerequisite for Nepal to achieve genuine and sustainable development, safeguarding its democratic future.